Intergroup Relations During the Refugee Crisis: Individual and Cultural Stereotypes and Prejudices and Their Relationship With Behavior Toward Asylum Seekers - Bye, Hege H. (Frontiers in Psychology, 2020)
In this paper, I investigate intergroup relations between natives and asylum seekers during the European refugee crisis, and contribute to the reemerging methodological debate on the measurement of stereotypes and prejudices as individual and collective constructs. Drawing on data from the Norwegian Citizen Panel (N = 1062), I examined how Norwegians stereotyped asylum seekers at the height of the refugee crisis and the emotional prejudices asylum seekers as a group elicited. By experimentally manipulating the survey question format, I examined whether and how stereotypes and emotional prejudices towards asylum-seekers differed depending on their measurement as individual or collective constructs. A subset of respondents (n =228) had reception centers for asylum-seekers established in their local community during the crisis. These participants reported their behaviors towards the asylum seekers in their neighborhood. In this subsample, I investigated how individual facilitating and harming intergroup behavior was related to individual and collective conceptualizations of stereotypes and prejudices. The results showed that both low warmth and low competence stereotypes, as well as negative emotions towards asylum seekers, were rated as stronger when measured as collective as compared to individual-level constructs. In the individual condition, respondents reported feeling more admiration and sympathy than respondents in the collective condition attributed to others. Individual stereotypes and prejudices correlated systematically with individual facilitating and harming intergroup behaviors. The perception that others hold more negative stereotypes of asylum seekers, and the perceived anger and fear of others, did correlated with individual harming behaviors. Perceptions of others’ anxiety correlated negatively with facilitating behaviors. Implications and future directions for the conceptualization and measurement of stereotypes and emotional prejudices are discussed.